Validity and reliability of the Turkish version of the 20?item jaw functional limitation scale - Yıldız, Nazım Tolgahan; Kocaman, Hikmet; Bingöl, Hasan (Taylor and Francis Ltd., 2024)
Purpose: This study aimed to translate the 20-item Jaw Functional Limitation Scale (JFLS-20) into Turkish (JFLS-20-TR) and investigate the psychometric properties of the JFLS-20-TR. Methods: This study included 232 patients with temporomandibular disorder (TMD) and 130 individuals without TMD. Structural (with confirmatory factor analysis [CFA]), convergent (with pain intensity, Fonseca Anamnestic Index [FAI], and Oral Health Impact Profile [OHIP-14]), discriminant (with maximum mouth opening [MMO]) and known-group validity were investigated to assess the construct validity. Cronbach’s alpha for internal consistency and the intraclass correlation coefficient (ICC2,1) for test-retest reliability were calculated. Additionally, content and face validity, smallest detectable change (SDC95), and floor/ceiling effects were evaluated. Results: According to CFA, the model fit indices were acceptable for JFLS-20-TR, confirming structural validity. Strong correlations were found between the global and subdomain scores of the JFLS-20-TR and pain intensity (r ? 0.80), FAI (r ? 0.83), OHIP-14 (r ? 0.76), and MMO (r ? ?0.79) scores, confirmed the convergent and discriminant validity of the JFLS-20-TR. In addition, JFLS-20-TR differentiated between patients with TMD and individuals without TMD (p <.05). Internal consistency (Cronbach’s alpha values: 0.91–0.93) was excellent, and test-retest reliability (ICC2,1 values: 0.91–0.95) was high. Content and face validity were satisfactory. The SDC95 values ranged from 0.79 to 1.43. No floor or ceiling effects were observed. Conclusion: The JFLS-20-TR is a valid, reliable, and useful tool for assessing jaw functional limitations in Turkish-speaking patients with TMD. © 2024 Taylor & Francis Group, LLC.
Keywords: factor analysis; Masticatory system; questionnaire; reliability and validity; temporomandibular disorder